Study of Antigenicity and Immunogenicity Gra1 Protein from Toxoplasma gondii - Didik T Subekti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Toxoplasmosis is known as zoonotic disease caused by Toxoplasma gondii infection. This microorganism has ability to evade immune system by forming parasitophorus vacuole (PV) formed through the phagosome vacuole modification by secreting dense granule protein (GRA). Among GRAs protein, GRA1 was selected as candidate for vaccine development. However, it remains controvercial whether the protein has adequate antigenicity and strong immunogenicity which are suitable for vaccine candidate. Some researcher reported that DNA vaccine of GRA1 was able to induce cellular mediated immunity and proinflamatoric humoral immunity. In fact, another study demonstrated that GRA1 protein was only antigenic based on their molecular weight and bioinformatic analysis.The other studies also showed that GRA1 was considered as weak immunogen based on bioinformatic studies. The ability of GRA1 protein to stimulate immune responses, both humoral and cellular mediated immunity were seemly caused by adjuvant.   Key words: Toxoplasma gondii, GRA1, cellular mediated immunity, humoral immunity